THE VALIDITY OF DIGITAL COMIC TO TRAIN METACOGNITIVE SKILLS ON REACTION RATE - Sunarto, Nadia Eka Vania; Hidayah, Rusly; Sumuba, Raizza Carbonel (Universitas Pakuan, 2024)
This research aims to determine the level of validity of digital comic media on reaction rate to practice developed metacognitive skills. This research is Research Development (RD) with the ADDIE model, through 5 stages, namely analyze, design, development, implement, and evaluate which is limited to the development stage. The instrument used to determine the level of validity is a validation sheet assessed by two chemistry lecturers and one chemistry teacher. The level of validity is obtained based on the value mode of the assessment results of three validators. Based on the results of the validation that has been carried out, the digital comic developed received a score of 4 which is categorized in each aspect of both content and construct which is categorized as valid. So it can be concluded that the digital comics developed are suitable for testing with students.